2019
DOI: 10.1055/s-0039-1677867
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Factors Affecting Coagulation Parameters at Birth in Preterm and Term Neonates: A Retrospective Cohort Study

Abstract: To date, few studies have investigated whether perinatal factors affect coagulation parameters at birth in preterm and term neonates. We retrospectively investigated coagulation factors on day 1 in 609 consecutive neonates admitted to our neonatal intensive care unit between January 2010 and December 2017. We measured coagulation factors on day 1 using peripheral blood samples. Multivariate analysis revealed that prothrombin time–international normalized ratio correlated with intraventricular hemorrhage (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
8
0
4
Order By: Relevance
“…Suzuki et al showed that plasma levels of thrombin-antithrombin complexes, D-dimer, fibrinogen, and fibrin degradation products in cord blood are higher in infants with birth asphyxia [19]. We previously described that maternal and neonatal complications such as birth asphyxia and PA affect coagulation parameters in preterm and term neonates [8]. In adults, most underlying conditions of DIC are reported to be infectious diseases, malignancies, trauma, and brain injury [1,20,21], while, we sometimes experience neonatal DIC with sepsis and necrotizing enterocolitis after birth; however, there were few cases of sepsisassociated neonatal DIC just after birth in the current study.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Suzuki et al showed that plasma levels of thrombin-antithrombin complexes, D-dimer, fibrinogen, and fibrin degradation products in cord blood are higher in infants with birth asphyxia [19]. We previously described that maternal and neonatal complications such as birth asphyxia and PA affect coagulation parameters in preterm and term neonates [8]. In adults, most underlying conditions of DIC are reported to be infectious diseases, malignancies, trauma, and brain injury [1,20,21], while, we sometimes experience neonatal DIC with sepsis and necrotizing enterocolitis after birth; however, there were few cases of sepsisassociated neonatal DIC just after birth in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…Of the 985 neonates admitted to our NICU between January 2010 and December 2017, 609 consecutive neonates born at 22-41 weeks were assessed for coagulation factors within the first 12 h of life, as previously described [8]. Of these, 366 neonates had at least one of underlying conditions and the remaining 243 neonates did not.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations